Ion Channels in Brain Metastasis - Klumpp, Lukas (MDPI, 2016)
Breast cancer, lung cancer and melanoma exhibit a high metastatic tropism to the brain. Development of brain metastases severely worsens the prognosis of cancer patients and constrains curative treatment options. Metastasizing to the brain by cancer cells can be dissected in consecutive processes including epithelial–mesenchymal transition, evasion from the primary tumor, intravasation and circulation in the blood, extravasation across the blood–brain barrier, formation of metastatic niches, and colonization in the brain. Ion channels have been demonstrated to be aberrantly expressed in tumor cells where they regulate neoplastic transformation, malignant progression or therapy resistance. Moreover, many ion channel modulators are FDA-approved drugs and in clinical use proposing ion channels as druggable targets for future anti-cancer therapy. The present review article aims to summarize the current knowledge on the function of ion channels in the different processes of brain metastasis. The data suggest that certain channel types involving voltage-gated sodium channels, ATP-release channels, ionotropic neurotransmitter receptors and gap junction-generating connexins interfere with distinct processes of brain metastazation.